(untitled) (International Journal of Engineering and Computer Science, 2014)
Recent advances in technology have given a new thrust to the satellite communication industry by deploying low cost very small aperture terminal (VSAT) network for data, voice, and video communication. VSAT networks are characterized by their low cost per node, integrated network management facilities, and support of multiple applications and integrated communication services. During the last five years, VSATs’ evolution has brought a significant change in the satellite communications industry, both in its current product offerings and future development strategies. In this paper, we propose an introduction to VSAT, architecture design of a VSAT network. Future trends in VSAT technology are also discussed